Nekateri vidiki vpliva ugleda na uspešnost podjetij v Sloveniji - Milfelner, Borut (Akademija MM, 2013)
Corporate reputation is seen as an important factor affecting company performance. In this paper, corporate reputation is conceptualized as a set of formative indicators, namely strategic orientation, trust, and attractiveness. The conceptual model of relationships between corporate reputation, market performance and financial performance is presented. The model was tested on a random sample of 464 companies in Slovenia with more than 20 employees. The results suggest that corporate reputation has stronger positive effect on market performance than on financial performance. Corporate reputation has both direct and indirect (through market performance) positive influence on financial performance. This paper shows that variables, such as loyalty, market share and sales volume, should be accounted for in reputation - performance relationship studies.
Keywords: podjetja; poslovna uspešnost; poslovni ugled; Slovenia; Slovenija